Penerapan Mobilisasi Miring Kanan dan Miring Kiri untuk Mencegah Dekubitus - Develin N. O. Woran (Jurnal Ilmiah Kesehatan, 2025)
Elderly with stroke have a high risk of experiencing pressure ulcers due to limited mobility. Pressure ulcers can cause impaired skin integrity and other complications. The purpose of this case study is to obtain an overview of the application of right and left oblique mobilization in preventing pressure ulcers in elderly with stroke with impaired skin integrity at the Damai Ranomuut Manado nursing home. The method used is descriptive using a case study approach. The results showed that right and left oblique mobilizations had different impacts on each subject. In subject I, there was a decrease in redness in the area of ​​skin that experienced pressure, indicating an improvement in skin integrity. While in subject II, no significant changes were found. The conclusion of this case study is that right and left oblique mobilizations can help prevent pressure ulcers, but the results can vary depending on the condition of each patient. Suggestions and researchers should be that nurses more routinely perform right and left oblique mobilizations as independent interventions in preventing pressure ulcers, and pay more attention to the skin condition of elderly with stroke periodically so that preventive measures are more effective.